Pengaruh Partisipasi Anggaran, dan Sistem Pengendalian Intern Pemerintah dengan Komitmen Organisasi Sebagai Variabel Moderasi Terhadap Kinerja Manajerial pada Organisasi Perangkat Daerah (OPD) Di Provinsi Jambi - Syindy Cantika; Mukhzarudfa Mukhzarudfa; Gandy Wahyu Maulana Zulma (Universitas Batanghari Jambi, 2021)
This study examines the effect of budgetary participation, government internal control systems with organizational commitment as a moderating variable on managerial performance. The purpose of this study was to determine the effect of the above variables, either partial or moderation. The population of this study were all employees of the Regional Apparatus Organization (OPD) of mandatory government affairs related to basic services. The sampling technique used purposive sampling. Of the five OPDs that are included in mandatory government affairs related to basic services, there are 120 employees as respondents in this study. The method used in this research is multiple linear regression analysis and moderated regression analysis (MRA). The software used to process data in this study is SPSS version 25. The results of this study that budget participation has a positive and significant effect on managerial performance, government internal control systems have a positive and significant effect on managerial performance, organizational commitment is unable to strengthen the effect of budget participation on performance. Managerial, and organizational commitment is not able to strengthen the influence of the government internal control system on managerial performance.